Mycotoxins in Kenyan dairy cattle feed: Occurrence and mitigation using bentonite and fumonisin esterase additives - Kemboi, D.C. (Ghent University, 2023)
The dairy industry plays an integral role in the economy of most sub-Saharan African countries. Over the years the demand of milk and dairy products has increased leading to movement from pastoralism to intensive and semi-intensive systems. These intensive and semi-intensive systems rely on concentrates as a way of improving productivity. However, these concentrates have been shown to contain mycotoxins which are secondary toxic metabolites of fungi that affect animal health and productivity, as well as food safety.